UMPSA’s UNIMADANI Fertigation Project records harvest performance increase reaching RM8,000 - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
JERANTUT, 24 June 2025 – The Economic Generating Fertigation Project implemented by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) at Madrasah Darul Uloom Al-Islamiah, Sungai Salan, Jerantut, Pahang, under the Community Empowerment Programme initiative by the Ministry of Finance–Public Universities (Komuniti @UNIMADANI) 2024 continues to record positive achievements as it successfully produced nearly four tonnes of cucumber harvest with income reaching RM8,000 within a seven-day collection period.